Loss of the HIF pathway in a widely distributed intertidal crustacean, the copepod Tigriopus californicus - Graham, Allie M. (Proc Natl Acad Sci U S A, 2019)
Hypoxia is a major physiological constraint for which multicellular eukaryotes have evolved robust cellular mechanisms capable of addressing dynamic changes in O(2) availability. In animals, oxygen sensing and regulation is primarily performed by the hypoxia-inducible factor (HIF) pathway, and the key components of this pathway are thought to be highly conserved across metazoans. Marine intertidal habitats are dynamic environments, and their inhabitants are known to tolerate wide fluctuations in salinity, temperature, pH, and oxygen. In this study, we show that an abundant intertidal crustacean, the copepod Tigriopus californicus, has lost major genetic components of the HIF pathway, but still shows robust survivorship and transcriptional response to hypoxia. Mining of protein domains across the genome, followed by phylogenetic analyses of gene families, did not identify two key regulatory elements of the metazoan hypoxia response, namely the transcription factor HIF-α and its oxygen-sensing prolyl hydroxylase repressor, EGLN. Despite this loss, phenotypic assays revealed that this species is tolerant to extremely low levels of available O(2) for at least 24 h at both larval and adult stages. RNA-sequencing (seq) of copepods exposed to nearly anoxic conditions showed differential expression of over 400 genes, with evidence for induction of glycolytic metabolism without a depression of oxidative phosphorylation. Moreover, genes involved in chitin metabolism and cuticle reorganization show categorically a consistent pattern of change during anoxia, highlighting this pathway as a potential solution to low oxygen availability in this small animal with no respiratory structures or pigment.